2020
DOI: 10.1016/j.breast.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Reduced symptom burden with the support of an interactive app during neoadjuvant chemotherapy for breast cancer – A randomized controlled trial

Abstract: Objectives Neoadjuvant chemotherapy causes distressing symptoms, which have to be managed by patients at home. Assessing and acting upon relevant patient-reported symptoms regularly with the support of mHealth such as apps, has shown to decrease symptom burden and improve health-related quality of life (HRQoL). There is a lack of apps for patients with breast cancer which are tested in rigorous trials and only a few include interactive components for immediate clinical management. The aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
188
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(197 citation statements)
references
References 48 publications
(69 reference statements)
4
188
0
Order By: Relevance
“…As most patients undergoing neoadjuvant chemotherapy for breast cancer or radiotherapy for prostate cancer are treated on an outpatient basis, partially self-reliant management of symptoms is necessary. Several studies show decreased symptom burden [ 24 , 45 ], that patients appreciate using Interaktor, and that they feel secure [ 21 , 26 ]. The app is currently being evaluated in two randomized controlled trials that include patients with breast cancer and prostate cancer, with the hypothesis that using the app will improve symptom management, reduce symptom burden, and increase cost-effectiveness through a reduced consumption of health care services in comparison to standard care alone [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As most patients undergoing neoadjuvant chemotherapy for breast cancer or radiotherapy for prostate cancer are treated on an outpatient basis, partially self-reliant management of symptoms is necessary. Several studies show decreased symptom burden [ 24 , 45 ], that patients appreciate using Interaktor, and that they feel secure [ 21 , 26 ]. The app is currently being evaluated in two randomized controlled trials that include patients with breast cancer and prostate cancer, with the hypothesis that using the app will improve symptom management, reduce symptom burden, and increase cost-effectiveness through a reduced consumption of health care services in comparison to standard care alone [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of how Interaktor is used and perceived, including the impacts of individual factors, is warranted in order to support the interpretation of the clinical effects of using the app during treatment [ 45 ]. Therefore, this study aimed to describe engagement with the Interaktor app among patients with breast and prostate cancer during their treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies did not report on app usage. Only a few studies have reported improvements in quality of life [ 26 , 27 ]. App for monitoring pain and linked to the ability to escalate to a clinician might lead to improved symptom control [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diverse non-pharmacological modalities can not only improve fatigue, sleep and HRQoL, but can also strengthen the immune system ( Table 1 ). Digital health technologies for people with cancer include mobile apps for pain relief ( Yang et al, 2019 ), self-management ( Fjell et al, 2020 ; Kim et al, 2018 ), or videogames designed to promote physical exercise and mental empowerment in pediatric oncology patients ( Bruggers et al, 2018 ; Govender et al, 2015 ). Personalized digital interventions for oncology patients can provide diverse self-care modalities such as physical exercises, yoga, mindfulness meditations, and breathing exercises ( Supplementary Table S3 ).…”
Section: Precision Digital Interventions For Epilepsy Pain Depression and Cancermentioning
confidence: 99%